New construction of enhanced cross Z-complementary set for generalized spatial modulation - PENG Xiuping; LIU Yinna; WANG Yu; NIU Xiaoxia (Tongxin xuebao)
In order to expand the existence space of enhanced cross Z-complementary set (E-CZCS), based on the extended generalized Boolean function (EGBF), the direct construction method of enhanced cross Z-complementary sets was proposed. The constructed q-ary E-CZCS had flexible and variable size, and their length was no longer limited to the traditional power of two. At the same time, the obtained enhanced cross Z-complementary sets was used as the training sequence of the generalized spatial modulation (GSM) system for channel estimation. The simulation results show that the enhanced cross Z-complementary sets can achieve optimal channel estimation. This presumably provides greater flexibility in the selection of training sequences in generalized spatial modulation systems.